Factors associated with posttraumatic growth in patients with severe burns by treatment phase - Sun‐mi Hwang; Eun Ju Lim (Wiley, 2020)
Abstract Aim This study aimed to identify differences in the level of depressive symptoms, social support and posttraumatic growth among patients with severe burns by treatment phase and the factors associated with posttraumatic growth in the acute and rehabilitation phases. Design A cross‐sectional descriptive design. Methods The factors associated with posttraumatic growth in 179 patients with severe burns were assessed using regression analysis. Results Compared with those in the acute phase (mild depression), those in the rehabilitation phase showed moderate depression and lower positive self‐perception, resulting in a significant difference in the means. Social support was significantly correlated with posttraumatic growth and explained 14.9% of its variance in the acute phase. Depressive symptoms and social support were significantly associated with posttraumatic growth and explained 28.2% of its variance in the rehabilitation phase. Therefore, the need for counselling support and intervention for patients with severe burns is evident.